The issue of scientific and methodological support of students during the period of continuous educational practice - Muhsinjon Mamadalievich Yusupov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is devoted to the scientific and methodological support of students of "Primary Education" in the organization and conduct of internships. Its relevance is that when a future teacher becomes acquainted with the first pedagogical activity, he feels the need for the necessary scientific and methodological resources. Most students do not have a degree in pedagogical colleges and do not have pedagogical knowledge, and the need for scientific and methodological support during the internship due to the fact that the main specialties are taught in 2-3 courses.